On the C/edge linking mechanism. Evidence from Polish - Sopata, Aldona (Lingua Posnaniensis, 2017)
Aldona Sopata. On the C/edge linking mechanism. Evidence from Polish. The Poznań Society for the Advancement of the Arts and Sciences, PL ISSN 0079-4740, pp. 87-100 The main aim of the paper is to examine Polish data from the perspective of Sigurðsson’s (2011, 2014) theory of C/edge linking. The crucial point of the theory lies in the hypothesis that phases are equipped with silent edge features which enable narrow syntax to link to context. All definite arguments, overt as well as null arguments, must be successfully C/edge linked, e.g. they have to match at least one feature in the broad C-domain. The present study focuses on utterances in Polish with direct object expressed as pronoun or null.The account proves successful in explaining some distributional patterns of null vs. pronoun objects in Polish. The Polish data investigated in this study indicates that the theory of silent edge linkers providing a communication channel for syntax and context is a step towards understanding the relation between syntax and pragmatics better.